Field Trip Report: Loita Hills, Narok - Bedelian, Claire; Notenbaert, An Maria Omer (International Livestock Research Institute, 2024)
A reconnaissance visit was made to the Loita Hills, Narok County to explore opportunities for developing both short-term and potential long-term activities aimed at addressing the ongoing land-use transition while promoting sustainable land management. The Loita Hills are experiencing a major transformation from communal to individual land ownership, creating both opportunities and challenges for local livelihoods, sustainable development, and forest conservation. The visit involved field observations and community discussions to gain a better understanding of land tenure and land use dynamics, local livelihoods, and potential intervention activities in collaboration with local stakeholders. Areas visited included the plains, the forested areas, and the community-managed Loita Naimina Enkiyio Forest. Discussions with community members and stakeholders provided insights into the challenges, priorities, and potential pathways for a sustainable transition.